Subtype frequency, demographic features, treatment and outcome of Juvenile Arthritis in one Centre in Abu Dhabi in the United Arab Emirates - K. Khawaja; R. Kalas; N. Almasri (BMC, 2023)
Abstract Background Juvenile Idiopathic Arthritis is a chronic inflammatory disease that affects 1 in 1000 children worldwide. Our population in the United Arab Emirates is diverse. The objective of this study is to describe the subtype frequency, demographic features and treatments received and outcome of our patients. Methods Patients with the diagnosis of Juvenile Arthritis identified through the hospital electronic medical records system (EMR), which was implemented for all medical documentation in January 2011. All patients included are patients who presented to our center for treatment and follow up from 2011 to end of 2021. Retrospective case notes review of patients electronic medical records with the diagnosis of JIA was performed. Results One hundred thirty-eight patients in total. Oligoarticular subtype was the most represented with 75 patients (55%) followed by Rheumatoid factor negative polyarticular JIA with 32 patients (23%) then Enthesitis related arthritis (ERA) with 10 patients (7%) then psoriatic (6%) then systemic JIA (5%). Undifferentiated subtype of 2%. The most diagnostic delay is in enthesitis related arthritis subtype with a mean of 11.4 months (6-25) followed by undifferentiated JIA with a mean of 7.5 months (4-8.5). 131 (96%) out of 138 received steroid treatment. Only 6 patients did not receive steroids. Out of 138 patients, 101 (73%) were on synthetic disease modifying medication methotrexate. Sixty-eight patients out of the total 138 required biologic treatment (49%). In total 93 patients achieved clinical remission (67%). In remission on treatment 78 patients which is (56%) of the total number of patients with follow up ranging from 1 to 5 years and 84% of patients in remission. In remission off treatment 15 patients (11% of all patients and 16% of patients in remission). Conclusion The most common subtype in our cohort of patients is oligoarticular JIA. Longest delay is for ERA subtype. All our patients with oligoarticular JIA received Intra articular steroid injection as first line treatment. 49% of our patients received biologic treatment similar to rate in Northern Europe. Our remission rate is 67% with 11% of patients are in remission off treatment. Access to care remains a priority to treat patients effectively.